(untitled) (Current Horticulture, 2024)
The semio-chemicals in general have environmental benefits associated with their use, in contrast to conventional insecticides. These semio-chemicals are inherently different from synthetic insecticides in terms of their mode of action and subsequent impact on the environment and human health. Although a number of outstanding successes have proved the potential of pheromone technology, the use of semio-chemicals is still in its early stages in India. It can be safely predicted that, as farming practices, the demand for semio-chemical technology will increase steadily which requires continuous and equal efforts of researchers, industry and farmers. Development of semio-chemical based push pull strategies using pheromones, repellents of insect pests and attractants of bio-agents for the management of insect pests in citrus (Citrus spp.) and citrus based farming systems needs immediate attention as these are known to be eco-friendly insect pest management strategies.